Development Of A Peptide-Based Antibody Assay To Detect Chikungunya Virus (Chikv) - Yew, Sze Shin (2013)
Chikungunya virus (CHIKV), first reported in 1953 in Tanzania, had reemerged in high magnitude after 2006 in tropical countries as well as spread into non-tropical regions. Chikungunya virus infection can cause viral fever with a side effect of severe and prolonged arthritis. Due to its similar clinical manifestation and geographical distribution with Dengue fever, a rapid detection kit to differentiate them is important to prevent misdiagnosis and provide effective medical care to the patient. Existing detection methods include time-consuming virus culturing and isolation, expensive technology requiring polymerase chain reaction (PCR) and less sensitive antibody targeting serological tests. This study was carried out to develop a simple and effective virus detection assay at the acute stage by targeting the surface exposed viral glycoprotein. The gene encoding E2, which is the glycoprotein that positioned on the viral spike and mandatory in receptor recognition, was cloned and expressed in E. coli system. However, the recombinant protein was insoluble. Further optimization on expression conditions and change of expression vector was not helpful either. Therefore, truncated E2 protein without hydrophobic C-terminal was constructed. However, it was also produced insoluble inclusion body. The inclusion body of E2 protein was solubilized with urea, then refolded and purified. Nevertheless, the yield and purity of the protein was not satisfying. Due to difficulty in preparing soluble and pure glycoprotein, the short peptide which is easy to produce with high purity was employed to produce mono-specific anti-CHIKV polyclonal antibodies.